2009
DOI: 10.1097/brs.0b013e3181b96187
|View full text |Cite
|
Sign up to set email alerts
|

Simple Oblique Lumbar Magnetic Resonance Imaging Technique and its Diagnostic Value for Extraforaminal Disc Herniation

Abstract: In light of this data, we suggest that oblique lumbar MRI can precisely demonstrate nerve roots in foraminal and extraforaminal areas. This technique is a simple and useful diagnostic tool for extraforaminal lumbar disc herniations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 11 publications
0
26
0
Order By: Relevance
“…Traditionally, herniated lumbar discs have been diagnosed by conventional magnetic resonance imaging (MRI) [6]. However, conventional MRI is inadequate for evaluating sciatica, because it may not clearly identify pathologic extraforaminal lesions or nerve root compression in the extraforaminal area [7]. Considering these shortcomings, better diagnostic imaging techniques that can detect lumbar nerve root entrapment are imminently required.…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, herniated lumbar discs have been diagnosed by conventional magnetic resonance imaging (MRI) [6]. However, conventional MRI is inadequate for evaluating sciatica, because it may not clearly identify pathologic extraforaminal lesions or nerve root compression in the extraforaminal area [7]. Considering these shortcomings, better diagnostic imaging techniques that can detect lumbar nerve root entrapment are imminently required.…”
Section: Introductionmentioning
confidence: 99%
“…The exiting spinal nerve root runs obliquely through the intervertebral foramen in an inferior-ventral direction391420). Thus, an oblique sagittal MRI view can show foraminal and extraforaminal lesions more accurately than a conventional saggital view11). For this reason, we used an oblique sagittal MRI view in all participants to obtain a more reliable and accurate diagnosis of symptomatic FEFDH.…”
Section: Discussionmentioning
confidence: 99%
“…There are several types of lumbar disc herniation, the most common one is postero-lateral protrusion of the disc into the spinal canal with compression of the traversing root. However, there are also relatively unusual disc herniations in particular locations, previously considered rare, which are increasingly identified as a consequence of improvements in imaging techniques710112226). These disc herniations include the foraminal or extraforaminal pathologies first described by Abdullah et al1) in 1974.…”
Section: Introductionmentioning
confidence: 99%
“…However, some of these methods can be problematic because of their complexity or lack of sensitivity and specificity (eg, conventional MRI, 93% and 52%, respectively) [16]. Recently, MRI techniques (eg, oblique sections [17], coronal section and MR myelography [16], and diffusion tensor image [18]) for diagnosing lumbar ie-FS have been developed and have indicated that the lumbar spinal nerve damaged in e-FE swells and runs transversely. Such pathognomonic findings are very useful for diagnosing e-FE, but although the swelling of the lumbar spinal nerve is plainly visible, the degree to which the spinal nerve runs transversely is less clear.…”
Section: Introductionmentioning
confidence: 98%